Ultrasonic welding of dissimilar polymer and polymer composites - Soh, Chun Zhi (Nanyang Technological University, 2021)
The demand for composite structures is increasing in diverse fields such as aerospace, sports, automotive, and many more. Ultrasonic welding can produce high weld strength and it can be performed in an extremely short time as compared to other conventional joining methods. Ultrasonic welding of dissimilar polymer composites has been investigated by many researchers and would be deemed beneficial in the selection of materials. Elium is a novel acrylic thermoplastic resin as it can be cured at room temperature and can be used for many industries such as automotive, sports, energy, and many more. There is some research done on ultrasonic welding of Elium composite to Elium composite to understand the weld characteristics of this material. The objective of this final year project is to investigate the weld characteristics of Elium composite to dissimilar epoxy composite using a coupling layer and optimization of different weld parameters. Static lap shear tests were performed to qualify the weld strength. Since Elium composites cannot be welded directly to epoxy composites, a manufacturing strategy is conceptualized to create a thermoplastic coupling layer on top of the epoxy composite to create the desired interphase to improve the welding strength. Baseline comparison with welded Elium to epoxy composite without coupling layer and with Polymethylmethacrylate (PMMA) coupling layer yields a maximum lap shear strength of 2.95 MPa and 8.56 MPa respectively and showed a higher lap shear strength of 190% for joints with coupling layer. Comparison between Elium and PMMA coupling layer showed that Elium coupling layer yielded a much lower lap shear strength of 6.88 MPa. The interphase between epoxy and coupling layer resin is observed to have a rough texture from the images before the welding. After welding, little to no effect on the interphase was observed, however, texture change can be seen further above the interphase. The interphase at the penultimate layer was observed to have no changes indicating that the coupling layer at that layer is ineffective in increasing the bond strength. Features such as shear cusps, plastic deformation, fiber pullout, and fiber imprints were observed from the in-depth SEM investigation for maximum lap shear strength and were indicative of the strong bonds between adherend.